Talaqqi and Musyafahah Methods in Qur’anic Literacy Learning: A Literature Review in Qur’anic Education: (Metode Talaqqi dan Musyafahah dalam Pembelajaran Baca Tulis Al-Qur’an: Analisis Studi Kepustakaan Pendidikan Al-Qur’an) - Himmah Aliyah Taslim (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2026)
The techniques of talaqqi and musyafahah are fundamental approaches in the realm of Qur’anic education, concentrating on the authoritative and direct manner of delivering recitation. However, contemporary studies frequently limit their examination of these methods to their technical aspects and practical educational outcomes. This study aims to investigate the talaqqi and musyafahah techniques within the context of teaching the reading and writing of the Qur’an, utilizing a library research method grounded in a narrative literature review format. Data was collected from both historical and contemporary sources, which consisted of Qur’anic exegeses, hadith collections, turath literature, and relevant scholarly journal articles. The collected information was analyzed utilizing content analysis and thematic analysis techniques. The results suggest that talaqqi and musyafahah serve not just as practical teaching techniques but also as strategies rooted in deep theological and knowledge-based principles, which are evident in how the Qur’an was revealed and in the educational methods used by the Prophet Muhammad. The combination of recitation, documentation, ethical learning, and spiritual refinement (tazkiyah an-nafs) establishes these techniques as comprehensive teaching methods. This research aids in broadening the conceptual framework of Qur’anic education by emphasizing the importance of talaqqi and musyafahah in modern Islamic education, especially in preserving recitation accuracy, cultivating Islamic character development, and ensuring the ongoing transmission of scholarship.